Use the Distributive Property to rewrite the expression without parentheses. -6 (4x + 3)

Question

Use the Distributive Property to rewrite the expression without parentheses. -6 (4x + 3)

in progress 0
Thu Hương 3 days 2021-07-19T22:52:07+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-07-19T22:53:08+00:00

    Answer:

    -24x + -18

    Step-by-step explanation:

    -6 x 4 = -24

    -6 x 3 = -18

    making the expression -6(4x + 3) into

    -24 + -18

    hope this helped!

    0
    2021-07-19T22:53:20+00:00

    Answer:

    −24x−18

    Step-by-step explanation:

    −6(4x+3)

    =(−6)(4x+3)

    =(−6)(4x)+(−6)(3)

    =−24x−18

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )